Carbon Monoxide Conversion Using Functionalized Clay Material with Ptn+, H+ and (Ptn+/H+) Cations - Belhakem1, Ahmed; A. Ghomari2, Samia; Taleb1, Fawzi (Asian Journal of Chemistry, 2014)
Sodium acetate intercalated halloysites, functionalized with Ptn+, H+ and (Ptn+/H+) cations, were used as catalysts in the carbon monoxide conversion reaction. Experiments were carried out at 3.5 103 torr, 523 K and H2/CO ratio (about 2) or (H2/CO = 67 %/33 % v/v). Platinum ionic species, their distribution and average size particle were determined by X-Ray absorption near edge structure (XANES) and titration of adsorbed H2 by O2 techniques, respectively. The obtained results showed that CO conversions were higher with (Ptn+/H+) than with H+ or Ptn+ cations used as catalysts. These results were in accordance with the fact that H+ and Ptn+ combination generates a higher level of acidity. The activation/deactivation process showed that catalysts could be easily regenerated after each reaction by heating at 250 °C for 5 h. For the present study, a higher selectivity toward light hydrocarbons (C1-C4) was noticed. The catalysts nature, structure and texture played a major role on the quality and quantity of the final products.